The Importance of PET/CT Findings and Hematological Parameters in Prediction Of Progression In Sarcoidosis Cases - Tertemiz, Kemal Can; Ozgen Alpaydin, Aylin; Karacam, Volkan; Mersin, Seda; Bekis, Recep; Sevinc, Can (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Aim: We aimed to reveal the correlation of NLR rate, RDW and MPV values and with the findings of PET/CT regarding the prediction of disease progression and the clinical characteristics. Materials and methods: The treatment naive sarcoidosis cases, of whose PET/CT have been taken due to mediastinal lymphadenopathy of whose diagnosis have been confirmed by biopsy, were included in the study. Hematological parameters, clinical, radiological and PET/CT findings are evaluated. Results: 40 sarcoidosis and 40 healthy control cases were included in the study. NLR, RDW, MPV and the sedimentation values in the sarcoidosis group were determined statistically significantly higher. In patients having parenchymal involvement in PET/CT, the values of FVC%, DLCO, DLCO%, DLCO/VA and DLCO/VA% were determined significantly lower. High NLR and PET/CT LAP SUVmax values and low DLCO% values are statistically significantly correlated with one-year disease progression. For predicting the progression, for the NLR cut-off value 3.20, the area under the curve was determined as 0.79 (CI 62.2-96.5), sensitivity as 80.0%, specificity as 76.7% and for the PET/CT SUVmax cut-off value 9.5, the area under the curve was determined as 0.71 (CI 46.6-95.9), sensitivity as 70.0%, specificity as 82.1%. Conclusion: We determined that the values observed in routine hematologic examinations such as NLR, RDW and MPV, were high in sarcoidosis cases. In addition, the values of NLR, DLCO% and PET/CT SUVmax might be used in predicting the progression. At the same, once again we showed that the lung parenchyma involvement in PET/CT correlates with many pulmonary function parameters.